How do Competing Interest Groups Influence Environmental Policy? The Case of Renewable Electricity in Industrialized Democracies, 1989–2007. (18th February 2013) - Cheon, Andrew; Urpelainen, Johannes
Abstract : In this article, we examine the effect of competing interest groups on environmental policy. We argue that the supporters of environmental policy should be the most influential in the absence of opposition, while the opposition's importance is maximized when the supporter coalition is strong. This highlights an important asymmetry between competing interest groups: supporters are decisive in the absence of opposition, while the opposition is only relevant if the supporters are already strong. We test the argument against data on renewable electricity generation in nineteen OECD countries, 1989–2007. Heavy industries have particularly strong incentives to oppose policies that support renewables, because heavy industries' profitability depends on inexpensive electricity. We find that the supporter coalition has a positive effect on the growth of renewable electricity generation, but the positive effect diminishes with the strength of manufacturing. Moreover, heavy industry has a negative effect on the growth of renewable electricity generation and this effect increases with the strength of the supporter coalition.